2015
DOI: 10.1111/jdv.12996
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of scalp and nail lesions with ixekizumab in a phase 2 trial in patients with chronic plaque psoriasis

Abstract: Ixekizumab monotherapy improved scalp psoriasis quickly with maintenance of clinical response and complete resolution of plaques in the majority of patients. Additionally, over 50.0% of patients with nail psoriasis experienced complete resolution of nail lesions by OLE week 48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 31 publications
0
51
0
2
Order By: Relevance
“…A modified NAPSI was used in 22% of studies with assessment on scales of 0–24 (degree of severity for nail matrix and nail bed features), 0–96 (degree of severity for each nail matrix and bed feature assessed separately in each quadrant), 0–14 (degree of severity for crumbling, onycholysis and pitting only) or on a scale that was not defined . A NAPSI of multiple nails was used in 20% of studies, with assessment of all fingernails and/or toenails, a single‐hand or all fingernails excluding the thumbnails . The majority of (mostly ongoing) studies (46%) did not adequately report the characteristics of NAPSI (to be) used.…”
Section: Resultsmentioning
confidence: 99%
“…A modified NAPSI was used in 22% of studies with assessment on scales of 0–24 (degree of severity for nail matrix and nail bed features), 0–96 (degree of severity for each nail matrix and bed feature assessed separately in each quadrant), 0–14 (degree of severity for crumbling, onycholysis and pitting only) or on a scale that was not defined . A NAPSI of multiple nails was used in 20% of studies, with assessment of all fingernails and/or toenails, a single‐hand or all fingernails excluding the thumbnails . The majority of (mostly ongoing) studies (46%) did not adequately report the characteristics of NAPSI (to be) used.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy findings for patients with plaque psoriasis, including PASI, sPGA, percentage BSA, NAPSI, PSSI, DLQI and Itch NRS, were consistent with 12-week phase 3 studies, 5 the short-term results in Japanese patients, 6 the long-term, 52-week global study, 4 and a post-hoc analysis of scalp and nail psoriasis from a phase 2 psoriasis study. 13 In mostly Caucasian patients, ixekizumab treatment for 52 weeks resulted in 77% of patients with a PASI 75 at the 52-week end-point. 4 In our study in Japanese patients, ixekizumab treatment for 52 weeks resulted in 92.3% of patients with a PASI 75 at the 52-week end-point.…”
Section: Discussionmentioning
confidence: 99%
“…Papp et al, 15 Lebwohl et al, 16 Papp et al, 28 Nakagawa et al, 29 Papp et al, 30 Mease et al 31 Ixekizumab Leonardi et al, 32 Gordon et al, 34 Saeki et al, 35 Langley et al, 36 Griffiths et al, 45 Yamasaki et al 46 Etanercept 1065 4 (0Á4)…”
Section: Incidence Of Candida Infection During Secukinumab Treatmentmentioning
confidence: 99%
“…33 Four of the selected ixekizumab studies reported no incidences of Candida infection over their duration (Table 2). 32,[34][35][36]…”
Section: Treatment With Brodalumab and The Prevalence Of Candida Infementioning
confidence: 99%